The Effect of Stocking Densityon the Growth andSurvival Of Red Nile Tilapia Seeds (Oreochromisniloticus) With Bioflok Technology On Peat Swamp Waters - Nurmi Yaningsih; Iskandar Putra; Mulyadi Mulyadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis research was conducted on August 3 until September 3 on 2017 at Aquaculture Technology Laboratory, Department of Aquaculture, Faculty of Fisheries and Marine University of Riau. The purpose of this research is to know the best stocking density on growth and survival of red nile tilapia seeds(Oreochromisniloticus) with bioflok system on peat swamp waters. The method used is Completely Randomized Design (CRD) with 1(One) factor consisting of 4(Four) treatment levels and three replicates (12 Unit aquariums). The standard of treatment used is stocking density 60 heads per container, 70 heads per container, 80 heads per container, and 90 heads per container. During 30 days maintenance of the best treatment on stocking density 60 heads per container with an absolute weight of 1.59 gram, absolute length 2.38 grams, daily growth rate 2.77% days, efficient feed 87.22%, feed conversion ratio 1,15 and 87.22% of survival rate.Key word : Red nile (Oreochromisniloticus),stocking density, bioflok system, Peat Swamp Water